College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Chapter P Review - Exercises - Page 77: 113


No solutions.

Work Step by Step

We solve the equation: $\displaystyle \frac{x+1}{x-1}=\frac{3x}{3x-6}$ $\displaystyle \frac{x+1}{x-1}=\frac{3x}{3(x-2)}$ $\displaystyle \frac{x+1}{x-1}=\frac{x}{x-2}$ First we cross-multiply: $(x+1)(x-2)=x(x-1)$ And distribute: $x^{2}-x-2=x^{2}-x$ And combine like terms: $x^{2}-x^{2}-x+x-2=0$ $-2=0$ Since we get a nonsensical equation, there are no solutions.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.